Ultrasound assisted green protocol for the synthesis of quinoxaline based bisspirooxindoles: crystal structure analysis, enone umpolung, DFT calculations, anti-cancer activity, and molecular docking studies - Baddepuri, Sravanthi; Allaka, Bhargava Sai; Gamidi, Rama Krishna; Faizan, Mohmmad; Pawar, Ravinder; Basavoju, Srinivas (Synthetic Communications, 2023)
A series of novel quinoxaline based bisspirooxindolo-pyrrolizidines were synthesized through 1,3-dipolar cycloaddition under ultrasonication with shorter reaction time and good yields. The compounds were well characterized by various spectroscopic methods and finally single crystal X-ray diffraction method (4c, 4d). DFT energy calculations confirm the regioselectivity due to enone umpolung effect. The in vitro anti-cancer activity of the synthesized compounds (4a-s) shows that the compounds 4g and 4q exhibited good anti-cancer activity with IC50 values14.51 +/- 1.1 and 11.36 +/- 0.23 mu M against DU-145 prostate cancer cell line; and 16.78 +/- 0.95 and 14.28 +/- 0.64 mu M against Hela cervical cancer cell lines when compared to the standard anti-cancer drug doxorubicin (1.75 +/- 0.06 and 1.35 +/- 0.09 mu M). In silico molecular docking studies indicated that the synthesized compounds may serve as a potential lead for the further development of novel anti-cancer agents.
Keywords: Anti-cancer activity; bisspirooxindoles; DFT calculations; Hirshfeld surface; ultrasonication